2022
DOI: 10.1186/s41039-022-00181-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of motivation in MOOCs’ retention rates: a systematic literature review

Abstract: Although MOOCs platforms offer a unique way to provide information for a large cohort of participants, only a small percentage of participants complete MOOCs. The high number of dropouts in MOOCs is a key challenge, and the literature suggests that it can be affected by participants' motivation. However, it is not known how and to what extent motivation influences participants’ dropout in MOOCs. There is a need to provide an overview of the role of motivation in MOOCs’ retention. In this study, we aimed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 68 publications
(97 reference statements)
1
31
0
2
Order By: Relevance
“…Recently, we carried out a literature review using the algorithm: mooc [All Fields] AND student [All Fields] AND motivation on MEDLINE® database, we found 16 articles highlighting students’ motivation role in academic success [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. A recent work by Badali et al confirmed our conclusion also [ 67 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we carried out a literature review using the algorithm: mooc [All Fields] AND student [All Fields] AND motivation on MEDLINE® database, we found 16 articles highlighting students’ motivation role in academic success [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. A recent work by Badali et al confirmed our conclusion also [ 67 ].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the top two most cited studies are on self-regulated learning [29] [30]. Why some learners persist in their studies but not others have been a longstanding topic of educational research [35] and MOOCs have provided an opportunity to look at this problem at scale online. How students engage via self-regulated learning appears to be one of the most interesting factors to researchers.…”
Section: Resultsmentioning
confidence: 99%
“…An activity is more likely to be completed by people who are strongly motivated intrinsically ( Deci and Ryan, 2012 ). Students who are intrinsic motivation to study through MOOCs experience favorable emotions that increase their motivation to take part in such programs ( Deci and Ryan, 2012 ; Sun et al, 2019 ; Badali et al, 2022 ). Students who are intrinsically motivated are more enthusiastic about taking MOOCs.…”
Section: Hypotheses Developmentmentioning
confidence: 99%